Optimization of Production of Cendol Dawet Ice and Doger Ice on Pakde Carts Using Fuzzy Linear Programming - Marpaung, T.J.; Singarimbun , Apredo Suranta; Lumban Tobing, Wike Joesline; Manik , Yessi Mardina; Ismayadi (Talenta Publisher, 2024)
Fuzzy Linear Programming is a model that is often used to solve problems related to optimization problems. This research will discuss efforts to optimize the production of Es cendol dawet and Es doger drinks on PakDe's cart in order to obtain maximum profits with minimum expenditure, without reducing the quality of the goods produced. One method used to obtain maximum benefits is to model goals and constraints using linear programming. Solving fuzzy linear programming is assisted using the QM for Windows application. Calculation results using fuzzy linear programming, maximum income will be obtained if 45 servings of Es Cendol Dawet are produced and 45 servings of Es Doger are produced, so the profit obtained is IDR 450,000. The increase in profits is IDR 50,000 more than ordinary linear programming.